Aliphatic β-Blocked Ligands in POCOP Pincer Complex Synthesis - Hansson,Ruben (2025)
Introduction: Synthesis of novel aliphatic POCOP pincer complexes with β-blocking alkyl groups. Background: An issue with Aliphatic POCOP pincer complexes is that the sought-after C=M bond is unstable with previous attempts forming aromatic groups or decomposing completely under heating. By introducing β-blocking elements to the aliphatic POCOP pincer ligands could this mitigate the decomposition and the C=M bond could be maintained in the pincer complexes. Aim(s): Can an aliphatic POCOP β-blocking pincer complex be similar in stability and catalytic activity when compared to aromatic POCOP pincer complexes? Methods: Due to the sensitivity of alkyl phosphines towards water and/or dioxygen all syntheses were conducted under inert conditions. The synthesised complexes were characterised by using 1H and 31P NMR and also with single crystal XRD when possible. Results: [Pd(II)Cl2(CNMe)2] metal precursor formed complexes 2, 3 and 4 when reacted with ligand 1 and 2 at room temperature in non-polar solvents such as benzene or toluene. Chlorido Ligand abstraction and substitution was successful using AgBF4, but no carbene-metal double bond was observed. Ni(II), Pt(II) and Ru(II) did not form pincer complexes after extensive investigation of reaction conditions. Conclusion: Complexation using aliphatic POCOP pincer ligands with β-blocking alkyl groups was possible with Pd(II) resulting in five novel complexes. But thermal instability coupled with few possibilities for ligand substitution leaves catalytic applications limited with current ligand structures.
Keywords: Aliphatic; β-blocking; Palladium; POCOP; Pincer complexes; Inorganic chemistry.